A Survey on Security of Certificateless Signature Schemes. Issue 2 (3rd March 2016) - Chen, Yu-Chi; Tso, Raylin
Abstract: In cryptography, security models play important roles to define the security with potential attacks. Following the security models, a scheme is analysed to be secure or insecure against those considered attacks. However, certificateless signatures (CLSs) are well-known notions to solve the key escrow problem of identity-based signatures, but the adversaries' attack power is not well defined. In typical CLS setting, the full private key is composed of two parts that are respectively generated by two different parties, and therefore, the security models will be more complicate than other systems. In general, there are two types of adversaries in CLS, and further can be extended into many security levels due to attack power. In this paper, a comprehensive study focuses on the security models of CLSs. We not only consider two security issues, public key replacement, and strong unforgeability, but also revisit all feasible and potential adversaries' abilities. According to the research results, we show the generalization of security models which consists of all cases of the adversaries. Finally, we give a security comparison with literature works.